2022
DOI: 10.1515/ract-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Five decades of GSI superheavy element discoveries and chemical investigation

Abstract: Superheavy element research has been a strong pillar of the research program at GSI Darmstadt since its foundation. Six new elements were discovered along with many new isotopes. Initial results on chemical properties of the heaviest elements were obtained that allowed for comparing their behavior with that of their lighter homologs and with theoretical predictions. Main achievements of the past five decades of superheavy element research at GSI are described along with an outlook into the future of superheavy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 141 publications
0
5
0
Order By: Relevance
“…Both these facilities, as well as the others in the field at present (RIKEN [101] and GSI [102]) have been using sophisticated gas-filled recoil separators first proposed by Albert Ghiorso [103]. In these devices the newly produced isotope recoils out of the back of the thin target into a low-pressure gas (of the order of 0.1 torr) where the ion repeatedly suffers charge-changing collisions with the residual helium gas.…”
Section: Cyclotrons In Transuranic Element Researchmentioning
confidence: 99%
“…Both these facilities, as well as the others in the field at present (RIKEN [101] and GSI [102]) have been using sophisticated gas-filled recoil separators first proposed by Albert Ghiorso [103]. In these devices the newly produced isotope recoils out of the back of the thin target into a low-pressure gas (of the order of 0.1 torr) where the ion repeatedly suffers charge-changing collisions with the residual helium gas.…”
Section: Cyclotrons In Transuranic Element Researchmentioning
confidence: 99%
“…In the past decades, several research centres played crucial roles to advance the production and study of superheavy elements. We focus here on the program at GSI Darmstadt, Germany, where SHE studies have been a pillar of the research program for decades (a recent overview highlighting element discovery and chemical studies can be found in [7]) and also a lively nuclear spectroscopy program has been continuously conducted, see e.g. [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…One of the biggest challenges in low-energy nuclear physics is the synthesis and study of new superheavy nuclei (SHN). Systematic experimental research performed over the past 30 years has finally led, with the discovery of element 118, oganesson, to the completion of the 7th row of the periodic table [1][2][3][4][5]. Unfortunately, experimental attempts to go beyond Og have not been successful so far [2,[6][7][8][9], mainly due to the extremely low production cross sections.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic experimental research performed over the past 30 years has finally led, with the discovery of element 118, oganesson, to the completion of the 7th row of the periodic table [1][2][3][4][5]. Unfortunately, experimental attempts to go beyond Og have not been successful so far [2,[6][7][8][9], mainly due to the extremely low production cross sections. Many theoretical models have been developed aiming at describing the SHN synthesis process (see, e.g.…”
Section: Introductionmentioning
confidence: 99%